# If f(x) = 2x^{2} - 2x + 7 and g(x) = x^{2} + 9x -6, what is f(x) - g(x)?

**Solution:**

Given the functions f(x) and g(x)

f(x) = 2x^{2} - 2x + 7

g(x) = x^{2} + 9x -6

We know that

f(x) - g(x) = (2x^{2} - 2x + 7) - (x^{2} + 9x -6)

On further calculation

= 2x^{2} - 2x + 7 - x^{2} - 9x + 6

So we get

= 2x^{2} - x^{2} - 2x - 9x + 7 + 6

= x^{2} - 11x + 13

Therefore, f(x) - g(x) is (x^{2} - 11x + 13).

## If f(x) = 2x^{2} - 2x + 7 and g(x) = x^{2}+ 9x -6, what is f(x) - g(x)?

**Summary:**

If f(x) = 2x^{2} - 2x + 7 and g(x) = x^{2} + 9x -6, f(x) - g(x) is (x^{2} - 11x + 13).